Insight into impurity scavenging effect of gadolinium-doped ceria electrolytes. Issue 6 (15th April 2020) - Sun, Xiaoou; Wang, Tao; Yan, Duanting; Zhang, Guodong; Wang, Dejun; Wang, Chunliang; Liu, Runru
Abstract: In this study, Ce0.89+x Gd0.1−2x Srx Eu0.01 O2−δ (x = 0–0.04) ceramic electrolytes sintered at different temperatures were prepared and the impurity scavenging effect of Sr 2+ dopants on their grain boundary (GB) electrical properties were investigated. The phase compositions, microstructures, and ionic conductivities of the samples were investigated using X-ray diffraction, scanning electron microscopy, and AC impedance spectroscopy, respectively. The incorporation of Sr 2+ improved the overall GB conduction of the electrolytes by decreasing their GB area and space-charge potential. It hindered conduction to some extent by weakening the impurity dilution effect. The scavenging effect could be observed only when the sintering temperature was higher than the eutectic temperature of Si GB impurities. At low sintering temperatures, the Sr 2+ dopants could not scavenge the GB impurities and increased the GB impurity coverage proportion. The findings of this study provide insights into the optimisation of the GB electrical properties of oxygen-ion conductors by selecting appropriate dopants and sintering temperatures to induce the GB impurity scavenging effect. Highlights: Sr 2+ ions scavenge GB impurities at temperatures higher than the eutectic temperature. Sr doping increases the GB impurity coverage ratio at low sintering temperatures. Sr doping decreases GB area and space-charge potential. The addition of Sr weakens the impurity dilution effect.